The Impact of a National Clinician-led Audit Initiative on Care and Mortality after Hip Fracture in England: An External Evaluation using Time Trends in Non-audit Data. Issue 8 (August 2015) - Neuburger, Jenny; Currie, Colin; Wakeman, Robert; Tsang, Carmen; Plant, Fay; De Stavola, Bianca; Cromwell, David A.; van der Meulen, Jan
Abstract : Background: Hip fracture is the most common serious injury of older people. The UK National Hip Fracture Database (NHFD) was launched in 2007 as a national collaborative, clinician-led audit initiative to improve the quality of hip fracture care, but has not yet been externally evaluated. Methods: We used routinely collected data on 471, 590 older people (aged 60 years and older) admitted with a hip fracture to National Health Service (NHS) hospitals in England between 2003 and 2011. The main variables of interest were the use of early surgery (on day of admission, or day after) and mortality at 30 days from admission. We compared time trends in the periods 2003–2007 and 2007–2011 (before and after the launch of the NHFD), using Poisson regression models to adjust for demographic changes. Findings: The number of hospitals participating in the NHFD increased from 11 in 2007 to 175 in 2011. From 2007 to 2011, the rate of early surgery increased from 54.5% to 71.3%, whereas the rate had remained stable over the period 2003–2007. Thirty-day mortality fell from 10.9% to 8.5%, compared with a small reduction from 11.5% to 10.9% previously. The annual relative reduction in adjusted 30-day mortality was 1.8% per year in the period 2003–2007, compared with 7.6% per year over 2007–2011 ( P <0.001 for the difference). Interpretation: The launch of a national clinician-led audit initiative was associated with substantial improvements in care and survival of older people with hip fracture in England.